EXPLORING DIGITAL ENGLISH TEACHING STRATEGIES THROUGH DIFFERENTIATED LEARNING IN VOCATIONAL HIGH SCHOOLS IN SOUTH SUMATRA - Dodi Irawan; Hadiyanto; Bunga Ayu Wulandari; Eddy Haryanto (English Review: Journal of English Education, 2026)
This study investigates the implementation of digital English teaching strategies with a differentiated learning approach at Vocational High Schools (SMKs) in South Sumatra. The research aimed to explore how teachers integrate differentiated learning strategies into their teaching practices, focusing on content, process, and product differentiation. Data was collected through observations, teacher questionnaires, interviews, and document reviews. The results show that the integration of differentiated learning has been effective in meeting the diverse needs of students, with content being adapted to students' interests and learning styles. Process differentiation was implemented through grouping students based on their learning pace, and product differentiation encouraged collaboration and student presentations. However, challenges such as limited digital literacy, inadequate teaching resources, and a lack of infrastructure were identified as barriers. The study suggests that further professional development, better digital resources, and enhanced infrastructure are essential to maximize the potential of differentiated learning strategies.